Inhibitors of Cholinesterases in Pharmacology: the Current Trends - Pohanka, Miroslav (Mini reviews in medicinal chemistry, 2020)
Inhibitors of cholinesterases are a wide group of low molecular weight compounds with a significant role in the current pharmacology. Besides the pharmacological importance, they are also known as toxic compounds like military nerve agents. In the pharmacology, drugs for Alzheimer disease, myasthenia gravis and prophylaxis of poisoning by nerve agents can be mentioned as the relevant applications. Besides this, anti-inflammation and antiphrastic drugs are other pharmacological applications of these inhibitors. This review is focused on a survey of cholinesterase inhibitors with known or expected pharmacological impact and indications of their use. Recent literature with comments is provided here as well.
Keywords: galantamine; Humans; cholinergic anti-inflammatory pathway; Nerve Agents; cholinesterasy; rivastigmine; Insecticides; Alzheimerova nemoc; cholinesterasové inhibitory; Alzheimer disease; butyrylcholinesterase; huperzine; lidé; insekticidy; Cholinesterases; autoimunitní nemoci; Alzheimer Disease; myasthenia gravis; Autoimmune Diseases; nerve agents; Protein Binding; nervová bojová látka; Anti-Inflammatory Agents; vazba proteinů; antiflogistika; donepezil; Cholinesterase Inhibitors; Acetylcholinesterase